Lump Solutions, Lump-Soliton Interaction Phenomena and Breather-Soliton Solutions to a (3+1)-Dimensional Boiti-Leon-Manna-Pempinelli-Like Equation (Journal of Nonlinear Modeling and Analysis, 2024)
The (3+1)-dimensional Boiti-Leon-Manna-Pempinelli-like equation(BLMP-like equation) is introduced by the generalized bilinear operators $D_p$ associated with $p = 3.$ The lump solutions, lump-soliton interaction phenomena and breather-soliton solutions are discussed to the (3+1)-dimensionalBLMP-like equation based on the generalized bilinear method with symboliccomputation system Mathematica. In order to observe the behavior of thosesolutions, we fix the value of $z,$ then give the 3D-graphs of some solutions atdifferent times. We find a lump solution moved in oblique direction; a lump-soliton interaction phenomenon is appeared and disappeared along with thetime. We also see a kink-breather soliton moved in oblique direction.
Keywords: Interaction phenomena; Lump solution; (3+1)-dimensional Boiti-Leon-Manna-Pempinelli-like equation.